Effect Of Transition Metals Addition On The Nickel Oxide Catalyst Toward Reduction Behaviour In Carbon Monoxide Atmosphere - Norliza Dzakaria; Azizul Hakim Lahuri; Fairous Salleh; Tengku Shafazila Tengku Saharuddin; Alinda Samsuri; Mohd Ambar Yarmo (UPM Press, 2024)
Indexed by WOS/Scopus/ERA/MyCite